Employed mothers' constructions of motherhood - Gacuan-Ramos, Bernadette F. (College of Home Economics, University of the Philippines Diliman, 2020)
This qualitative study seeks to gain an in-depth understanding on how motherhood is constructed in the lived experiences of unpaid care work (UCW) and employment work (EW). Specifically, it aims to describe the lived experiences, characteristics, roles and functions, challenges, changes in self-concept and family perspectives and other influences in the construction of motherhood of employed mothers (EMs). Twelve full-time EMs from four occupational groups were invited through focused sampling for narrative interviews. The narratives were analyzed and interpreted based on their individual realities and experiences, and contextual background using thematic analysis that are coded and categorized according to emergent themes. The resulting constructions of motherood showed several nuances in EMs' self-concept and processes as they interact with their home and family, and their workplace. The narratives showed and emergent picture of an EM as a mother who poses an inner strength to blend UCW and EW. The narratives also showed an EM who is a supportive partner to the husband and a pragmatic worker. Results also showed that EMs' own constructions of motherhood were made possible because of their ability to recognize and adjust to the need for change, negotiate challenges and learn from their experiences, which resulted in an evolving notion of their being employed mothers. With these, findings of the study may help us better understand how families respond to change and enhance the way we aid families in navigating the changing world by highlighting their strengths and capabilities and improving support mechanisms.